Epidemiological investigation of feline infectious peritonitis in cats living in Harbin, Northeast China from 2017 to 2019 using a combination of an EvaGreen-based real-time RT-PCR and serum chemistry assays. (February 2020) - Guan, Xueting; Li, Hua; Han, Meijing; Jia, Shuo; Feng, Baohua; Gao, Xuwen; Wang, Zhuo; Jiang, Yanping; Cui, Wen; Wang, Li; Xu, Yigang
Abstract: Feline infectious peritonitis (FIP) is caused by the FIP virus (FIPV), a highly virulent mutant form of feline coronavirus (FCoV). This disease is one of the most important infectious diseases in cats, and it is associated with high mortality, particularly among younger cats. In this study, we isolated a wild-type FIPV HRB-17 epidemic strain from the blood sample of household pet cat exhibiting the characteristic wet-form FIP symptoms, which has been confirmed further by animal infection. Further, we developed an EvaGreen-based real-time RT-PCR assay for the accurate detection of FCoV based on the amplification of the highly conserved FIPV N gene. Then, using a combination of the real-time RT-PCR approach and a serum chemistry assay, we performed an epidemiological survey of FIPV infection in cats living in Harbin City, Northeast China. The results indicated that the EvaGreen-based real-time RT-PCR assay can be used for screening FCoV infection in the affected cats at an analytical detection limit of 8.2 × 10 1 viral genome copies/μL, but could not effectively distinguish FIPVs from FECVs. Additionally, the results of the epidemiological survey investigating feline blood samples (n = 1523) collected between July 2017 to July 2019 revealed an FIPV prevalence of approximately 12% (189/1523). Maybe, the prevalence would be less than 12% due to the real-time RT-PCR assay could not accurately differentiate FIPV and FECV. Nevertheless, it still highlighted the severity of the FIP epidemic in cats and reiterated the urgent need to develop effective anti-FIP therapeutic agents and anti-FIPV vaccines. As pet cats are household animals, risk communication and continuous region-extended surveillance cat programs are recommended. Highlights: Evolutionary relationship indicated genetic reassortment between FIPV HRB-17 strain and CCoV. EvaGreen-based real-time RT-PCR assay for FCoV was developed targeting the conserved N gene. Epidemiological survey of FIPV infection in cats was performed in Northeast China from 2017 to 2019. FIPV prevalence of 12.41% (189/1523) indicated the severity of FIPV infection in cats, China. Risk communication and continuous region-extended surveillance cat programs are recommended.